Morocco flexes economic muscles as it seeks AU reinstatement - Franck Kuwonu (Africa Renewal, 2017)
Slowly and steadily, Morocco has been establishing itself as a major economic force in sub-Saharan Africa, even as it eyes gaining readmission into the African Union (AU), which it left decades ago.